Smart Schools an Innovation in Education: Malaysian’s Experience - Mirzajani, Hassan; Bayekolaei, Mehraneh Delaviz; Kookandeh, Meysam Rajaby; Rezaee, Seyede Safoora Razzaghpoor; Kamalifar, Ali Akbar; Shani, Hassan Razaghi (Asian Journal of Education and Training, 2016)
According to the new environment created by the information period, training and learning new skills are being inevitable. Retraining the skills of group working to coordinate the information age has created special conditions for education. Smart schools are one of the strategies adopted by schools in response to today’s modern needs. Smart schools are active for entrepreneurship, using modern methods to improve the quality of education, and training qualified people who at any time have the capability and efficiency of modern industry. The purpose of this study, is the use of ICT in Malaysian Smart School and comparing it with the Smart Schools in Iran. To conduct this study, library, documents, Web sites and electronic journals are available. The results of this study show that although there are significant differences between the education system and deployment of ICT in Iran with the standards in smart schools in leading countries like Malaysia, according to the original development of smart schools in Iran which has been adapted from Malaysia, recognizing the realities of this action in Malaysia, can be effective in the development of schools in the country and prevent indiscriminate development.